2010
DOI: 10.3109/0142159x.2010.494740
|View full text |Cite
|
Sign up to set email alerts
|

Health advocacy training: Why are physicians withholding life-saving care?

Abstract: The societal responsibility of physicians to be health advocates, both at the population and patient level is necessary to positively influence public health and policy. Physicians must commit to learn about policy reform and the legislative process. Several regulatory physician organizations emphasize the importance of health. In addition, the Association of American Medical Colleges' (AAMC) Medical Schools Objectives Project, the Medical Council of Canada Qualifying Examination objectives and several Canadia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…The examples provided were largely experiential learning opportunities, such as rural non-clinical placements and the interactive panel discussions involving expert patients and representatives of community-based organisations. These examples are consistent with North American studies suggesting that it is largely through “community health improvement clerkships”, 9 research projects, 10 health policy workshops 11 and opportunities to collaborate with politicians on local health issues 11 where students learn to be health advocates.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The examples provided were largely experiential learning opportunities, such as rural non-clinical placements and the interactive panel discussions involving expert patients and representatives of community-based organisations. These examples are consistent with North American studies suggesting that it is largely through “community health improvement clerkships”, 9 research projects, 10 health policy workshops 11 and opportunities to collaborate with politicians on local health issues 11 where students learn to be health advocates.…”
Section: Discussionsupporting
confidence: 72%
“…Nonetheless, additional studies have demonstrated that optimal training in advocacy requires practical “hands-on” experience. 8 , 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing concern among physicians and medical teachers that medical students have insufficient patient contact and their training is task-focused rather than patient-focused (1)(2)(3)(4). Too often they ask "what is the problem?"…”
Section: Introductionmentioning
confidence: 99%
“…These sometimes do not focus on addressing health inequities. 9 Based on the current gaps in advocacy education-an identified basis of knowledge and skill, and a lack of attention to systemic and structural factors-we chose to develop an educational initiative based on Metzl and Hansen's Structural Competency paradigm. This initiative includes five intersecting knowledge and skill-sets, including recognizing the structures that shape clinical interactions, developing an extra-clinical language of structure, rearticulating "cultural" formulations in structural terms, observing and imagining structural interventions, and developing structural humility.…”
Section: Introductionmentioning
confidence: 99%